Teaching Methods Of Dictation And Elements Of Arabic Language/ طرائق تعليم الإملاء وعناصر اللغة العربية - Kusnawan, Wawan; Wargadinata, Wildana; Rasyidi, Abdul Wahab (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Many schools and schools of Islamic education in Indonesia revolve around the advancement of science and technology or philosophy, psychology, and sociology so that Muslims who come are not late for things they will accept and explain in their future lives. This study aims to discover the steps in learning imla to teach vocabulary. Detect and find out about the method used to teach superposition at Pondok Modern Darussalam Gontor. This study's results are as follows: the steps used for learning dictation are listening, reading, and writing for dictation letters, sentences, and essays. The measures used for teaching vocabulary start from the dormitory by giving vocabulary every day after the morning prayer. Each student repeats what the language movement from each dormitory says, writes it down, orders them to memorize it, puts the vocabulary in sentences, continues teaching it in class according to their respective categories, and writes vocabulary in several places according to their vocabulary. The steps used for superposition learning: the teacher starts writing examples on the blackboard, then asks the lesson of yesterday's lesson, explains the relationship between yesterday's class and the new lesson, and explains the rules of nahwu and shorof by example.